Care transition types across acute, sub-acute and primary care: Case studies of older people with complex conditions and their carers. Issue 3 (2nd July 2018) - Harvey, Desley; Foster, Michele; Quigley, Rachel; Strivens, Edward
Abstract : Purpose: The purpose of the paper is to examine the care transitions of older people who transfer between home, acute and sub-acute care to determine if there were common transition types and areas for improvements. Design/methodology/approach: A longitudinal case study design was used to examine care transitions of 19 older people and their carers as a series of transitions and a whole-of-system experience. Case study accounts synthesising semi-structured interviews with function and service use data from medical records were compared. Findings: Three types of care transitions were derived from the analysis: manageable, unstable and disrupted. Each type had distinguishing characteristics and older people could experience elements of all types across the system. Transition types varied according to personal and systemic factors. Originality/value: This study identifies types of care transition experiences across acute, sub-acute and primary care from the perspective of older people and their carers. Understanding transition types and their features can assist health professionals to better target strategies within and across the system and improve patient experiences as a whole.